Cabotegravir Is Not Associated With Weight Gain in Human Immunodeficiency Virus–uninfected Individuals in HPTN 077. (24th May 2019) - Landovitz, Raphael J; Zangeneh, Sahar Z; Chau, Gordon; Grinsztejn, Beatriz; Eron, Joseph J; Dawood, Halima; Magnus, Manya; Liu, Albert Y; Panchia, Ravindre; Hosseinipour, Mina C; Kofron, Ryan; Margolis, David A; et al.
Abstract: Studies in human immunodeficiency virus (HIV)–infected individuals suggest excess weight gain with integrase inhibitor–based antiretroviral therapy. The HIV Prevention Trials Network Study 077 evaluated changes in weight and fasting metabolic parameters in HIV-uninfected individuals randomized to cabotegravir or a placebo. No differences between arms were found for change in weight or fasting metabolic parameters overall or for subgroups.